Edukasi dan Pemeriksaan pada Ibu Hamil tentang Bahaya Infeksi Saluran Kemih pada Kehamilan - Nur Vita Purwaningsih; Rahma Widyastuti; Firdausi Nuzula; Ellies Tunjung Sari; Ainutajriani Ainutajriani; Tri Ade Saputro (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
Hormonal changes in pregnant women are a process of preparing for the birth of a baby, pregnant women are very sensitive to infections from various microorganisms. Urinary tract infection is the most common bacterial infection in pregnancy, increasing the risk of morbidity and mortality of mothers and newborns. A white blood cell count of more than 15,000/mm3 is an indication of infection in pregnant women. Caused by viral, bacterial and protozoal infections. Infection in pregnant women must be detected early, in order to prevent preterm labor. One of the tests that can be done is to count the number of erythrocytes and leukocytes. This study was conducted to determine the results of erythrocytes and leukocytes in pregnant women. Community service education for pregnant women about the dangers of urinary tract infections in pregnancy to educate and inform health. Community service activities in the form of creative education through the presentation of poster and presentations are carried out directly at the bancaran village hall. Community service activities in the form of creative education related to education for pregnant women about the dangers of urinary tract infections in pregnancy in the Bancaran sub-district area were carried out well, and received a positive enthusiastic response.